NILAI-NILAI PENDUKUNG KESANTUNAN DALAM BAHASA BANJAR:TINJAUAN PRAGMATIK - NFN Jahdiah diah (Multilingual, 2020)
Everyone needs speak politely. A person speaks and behaves politely for self-actualization. The use of language politeness is not only determined by the choice of words, but also by the attitude of the speaker to the speech partner or interlocutor. The objective of this study is to describe the supporting values of language politeness in the Banjar language. This study uses a descriptive method; it is a descriptive quantitative, this research consists of three steps, namely 1) collecting data, 2) data analysis, and 3 presenting the results of data analysis. This research data consists of various kinds of utterances in various social communication situations in the Banjar language speaker. This study uses a pragmatic theory, especially regarding the politeness scale of language by Robin Lakoff. The results show that the supporting values of politeness in the Banjar language are based on 1) humility, 2) empathy, 3) respect, 4) sacrifice and 5) introspective manner.